Pancreaticoduodenectomy for nonampullary duodenal lesions: indications and results. Issue 12 (December 2016) - Shamali, Awad; McCrudden, Raymond; Bhandari, Pradeep; Shek, Fanny; Barnett, Emily; Bateman, Adrian; Abu Hilal, Mohammed
Abstract : Background: Pancreaticoduodenectomy (PD) is a complex procedure, associated with a definite risk of mortality and 30–50% risk of complications. For nonampullary duodenal lesions, PD can carry a higher morbidity as they are more commonly associated with a soft pancreas and narrow-calibre main pancreatic ducts. It is therefore paramount that the risks and benefits of surgery are considered carefully in this group of patients. A preoperative histological diagnosis for duodenal lesions is normally achieved by endoscopic biopsy. In this study, we aim to assess the outcome of PD in patients with nonampullary duodenal lesions and correlate the preoperative endoscopic histology work-up with the definitive postoperative pathology. Materials and methods: We reviewed a prospectively collected PD database from January 2007 to December 2013. Demographic and clinical data were included. Preoperative endoscopic histology was compared with final specimen histology to assess concordance. Results: Forty patients (55% women, mean age 69.4 years, range 45–83 years) underwent PD for duodenal lesions over a 7-year time period. The most common presenting symptom was epigastric pain (32.5%), followed by anaemia (20%). Overall, the complication rate was 55%, with the most frequent adverse event being pancreatic fistula in 13/40 (32.5%). The perioperative mortality was 2/40 (5%). Duodenal adenocarcinoma (65%) was the most common postoperative histological diagnosis. The mean tumour size was 36 mm (range 5–103 mm) and a median of 13 nodes were harvested. The median length of stay was 15 days (range 7–66 days). Overall, 12/40 patients (30%) had a preoperative diagnosis of high-grade dysplasia. The postoperative specimen in this subgroup of patients was reviewed carefully and only 3/12 (25%) patients had high-grade dysplasia in the resection specimen. In the remaining patients, 3/12 (25%) had adenocarcinoma in the resection specimen and 6/12 patients (50%) had low-grade dysplasia. Conclusion: PD carries a high mortality and morbidity, especially for duodenal lesions. We recommend a careful endoscopic review after the index case with a high-definition optical evaluation of duodenal lesions. This, in addition to an experienced histological assessment of the index biopsy material, forms an essential prerequisite in aiding the multidisciplinary team in the decision-making process with respect to triage of these lesions to conservative management, surveillance, endoscopic resection or finally surgical resection.